EXPERIENCE OF TREATMENT WITH IBANDRONIC ACID IN PATIENTS WITH SEVERE RHEUMATOLOGICAL DISEASES AND SYSTEMIC OSTEOPOROSIS - A.O. Lisitsyn; E.I. Alexeeva; V.G. Pinelis; M.I. Bakanov; S.I. Valieva; T.M. Bzarova (Вопросы современной педиатрии, 2010)
This article presents the results of a study of effectiveness and safety of ibandronic acid in 21 children with rheumatologic diseases and severe systemic osteoporosis. The treatment with ibandronic acid during 48 weeks provided statistically significant increase of mineral density of bones, decrease of pain intensity, lessening of serum concentration of bone resorption marker — C-terminal telopeptide. The development of repeated compressive fractures of vertebrae and bones of peripheral skeleton at the time of treatment with this medication was not detected. Key words: children, rheumatological diseases, osteoporosis, treatment, bifosfonates, ibandronic acid.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(1):116-121)